(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article examines comparative lexicographic and translation aspects of terminology in the field of management psychology in Uzbek and Russian languages. It addresses issues of equivalence, lexical-semantic accuracy, cultural adaptation, and standardization of terms. Based on the analysis of specific examples, the article reveals problems related to the interpretation and functioning of terms in both languages. Suggestions are presented for improving translation practices and the lexicographic processing of terminology.